(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
The essay offers a general overview of the Law on the Amendment of the Russian Constitution, which was signed by the President on 14 March 2020 and will be submitted to popular ratification on the 1st of July. The article aims to highlight the shortcomings both in terms of the procedure followed, which was unusual, and of the Law’s contents, which reinforce Presidential competences and role. This is particularly significant as, as a general rule, the power distribution does not change when specific elements − already present in the legislation and in the institutional practice − are introduced at a constitutional level.